1998
DOI: 10.1016/s0168-9002(98)00765-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties of CsI(Tl) crystals and their optimization for calorimetry of high energy photons

Abstract: A photomultiplier setup for precise relative CsI(Tl) crystal light yield and uniformity measurements is described. It is used for wrapping material studies to optimize the uniformity and the yield of the light output of 36 cm long crystals. The uniformity is an important property in high energy photon calorimetry. Results of an optimization of photodiode coupling to crystals, the influence of temperature and radiation damage to light and photoelectron yield are also presented. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…One is a CsI(Tl) coupled to photodiode (PD) detectors that has been used to detect high energy gamma-rays. [3][4][5] The CsI(Tl)-PD detectors are more suitable because of their high stopping power, relatively low cost, and easy ability to be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…One is a CsI(Tl) coupled to photodiode (PD) detectors that has been used to detect high energy gamma-rays. [3][4][5] The CsI(Tl)-PD detectors are more suitable because of their high stopping power, relatively low cost, and easy ability to be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…and Preamplifier Assembly The photon detector consists of two 2 × 1 cm 2 silicon PIN diodes glued to a transparent 1.2 mmthick polysterene substrate that, in turn, is glued to the center of the rear face of the crystal by an optical epoxy [77] to maximize light transmission [78]. The surrounding area of the crystal face is covered by a plastic plate coated with white reflective paint [79].…”
Section: Photodiodesmentioning
confidence: 99%
“…The resulting signal distribution had a mean and rms width of 7300 and 890 photoelectrons/MeV, respectively; none of the crystals had a signal of less than 4600 photoelectrons/MeV [78,80].…”
Section: Photodiodesmentioning
confidence: 99%
“…The peak scintillation wavelength of CsI(Tl), around 550 nm, is well matched to the photodiode response. Reports in the literature on the optimisation of CsI(Tl) scintillator/ photodiode detector systems have shown that the coating of the scintillator in reflective layers gave optimum results [8,9].…”
Section: Gamma-ray Detector Arraymentioning
confidence: 99%